Biochemical and histopathological studies on patients with mucopolysaccharidoses, two of whom had been treated by fibroblast transplantation. Issue 4 (April 1983) - Crow, J; Gibbs, D A; Cozens, W; Spellacy, E; Watts, R W
Abstract : Biochemical and pathological observations on tissues from two patients with Hurler disease (mucopolysaccharidosis IH; alpha-L-iduronidase deficiency) who had been treated by fibroblast transplants as a means of enzyme replacement treatment are reported. These results and those obtained in three surgical specimens [ligamentum flavum with dura mater from a case of Scheie disease (mucopolysaccharidosis IS; alpha-L-iduronidase deficiency); a fetus with Hurler disease; and tonsil from a patient with Hunter disease (mucopolysaccharidosis II; alpha-L-idurono-2-sulphate sulphatase deficiency)] illustrate the inadequacy of routine histological processing to demonstrate the abnormal glycosaminoglycan accumulation in this group of diseases. A combined approach using histochemistry and electron microscopy enables the extent of both extracellular and intracellular involvement to be assessed. The fetus (20 wk gestation) already showed evidence of Hurler disease. The pathological appearances in both of the fibroblast-transplanted patients were those which would have been expected in patients dying with unmodified Hurler disease. There was no detectable alpha-L-iduronidase activity in the brain, liver, kidney or in fibroblasts cultured from either the transplantation sites or from remote subcutaneous sites in either of the transplanted patients. These results are discussed from the viewpoint of their bearing on the pathophysiology of the mucopolysaccharidoses and proposals for their treatment by enzyme replacement.